Proton minibeam radiation therapy widens the therapeutic index for high-grade gliomas. Issue 1 (December 2018) - Prezado, Yolanda; Jouvion, Gregory; Patriarca, Annalisa; Nauraye, Catherine; Guardiola, Consuelo; Juchaux, Marjorie; Lamirault, Charlotte; Labiod, Dalila; Jourdain, Laurene; Sebrie, Catherine; Dendale, Remi; Gonzalez, Wilfredo; et al.
Abstract Proton minibeam radiation therapy (pMBRT) is a novel strategy which has already shown a remarkable reduction in neurotoxicity as to compared with standard proton therapy. Here we report on the first evaluation of tumor control effectiveness in glioma bearing rats with highly spatially modulated proton beams. Whole brains (excluding the olfactory bulb) of Fischer 344 rats were irradiated. Four groups of animals were considered: a control group (RG2 tumor bearing rats), a second group of RG2 tumor-bearing rats and a third group of normal rats that received pMBRT (70 Gy peak dose in one fraction) with very heterogeneous dose distributions, and a control group of normal rats. The tumor-bearing and normal animals were followed-up for 6 months and one year, respectively. pMBRT leads to a significant tumor control and tumor eradication in 22% of the cases. No substantial brain damage which confirms the widening of the therapeutic window for high-grade gliomas offered by pMBRT. Additionally, the fact that large areas of the brain can be irradiated with pMBRT without significant side effects, would allow facing the infiltrative nature of gliomas.